Értékteremtés a közlekedésben a határmenti közlekedési közszolgáltatások fejlesztésével - Feketéné Benkó, Kata (Közép-Európai Közlemények, 2024)
The territories and borders of the countries in Europe changed a lot during the last century, which had a positive effect on some states and a negative effect on others, but in all cases it can be said that it led to a reorganization of territorial processes. In addition to Hungary’s territorial loss, it does not have a border region where the new state border would not have split a naturally formed region in two. Borders, among other things, by eliminating transport options, turned the border areas into „backwaters”, which led to their devaluation. The aim of the research is to prove that the specific aspect of value creation is the creation of cross-border transport, within this, the realization of transport accessible to everyone by creating the availability of public transport services. The purpose of cross-border transport is to improve the situation of two peripheral areas that exist side by side, but are incapable of lasting cooperation with each other due to the lack of transport connections. The first stage of connections is the existence of the infrastructure, on which certain activities can be carried out, such as individual modes of transport, organized group transport and goods transport. However, the existence of public transport or public transport services occupies a special place in the formation of regions. During the research, in addition to the state of the infrastructure, different public transport services were mapped and compared, and the value-creating power of public transport services was verified by comparing social and economic phenomena.